Culturing for conservation: the need for timely investments in reef aquaculture - Ridlon, April D.; Grosholz, Edwin D.; Hancock, Boze; Miller, Margaret W.; Bickel, Aric; Froehlich, Halley E.; Lirman, Diego; Pollock, F. Joseph; Putnam, Hollie M.; Tlusty, Michael F.; Waters, Tiffany J.; Wasson, Kerstin (Frontiers in Marine Science, 2023)
Temperate oyster and tropical coral reefs are analogous systems that create habitat for economically, ecologically, and culturally important species, and they provide countless ecosystem services to human coastal communities. Globally, reefs are imperiled by multiple anthropogenic stressors, particularly climate impacts. Using aquaculture to support conservation goals - known as conservation aquaculture - is a relatively new approach for many reef building species, but it shows great promise for promoting species recovery and bolstering resilience to stressors. Concerns about aquaculture-associated risks, both known and potential, have often restricted the implementation of this tool to an emergency intervention following dramatic declines on reefs, when species or systems were unlikely to recover. Here, we combine expertise from coral and oyster reef ecosystems to consider the role of aquaculture as a conservation intervention for reefs, and provide recommendations for its timely development and targeted implementation. We highlight the importance of evaluating reef systems - alongside local stakeholders and Indigenous communities - to determine where and when the benefits of using aquaculture are most likely to outweigh the risks. We spotlight the importance of proactive monitoring to detect reef population declines, and the value of early aquaculture interventions to increase efficacy. Novel aquaculture approaches and technologies specifically designed for reef builders are considered, including techniques for building complex, multi-generational and multi-species reefs. We address the need for scaling up aquaculture-assisted reef recovery, particularly of corals, using high volume methods like those that have been successfully employed for oysters. We also recommend the immediate assessment and development of techniques to increase climate resilience of reef builders and we identify the challenges and trade-offs of these approaches. We highlight the use of proof-of-concept projects to test these promising methods, and we advise tracking of all interventions over time to determine their long-term efficacy. Finally, we outline opportunities to leverage novel partnerships among conservation, industry, and community interests that utilize aquaculture to facilitate the conservation of reefs. Developing conservation aquaculture approaches now is critical to position managers, scientists, and restoration practitioners to implement this intervention in timely and effective ways to support resilient reef and human communities worldwide.